Digitalizing School Management: Achieving Excellence through Technology Integration in Primary Schools in Indonesia - Herry Sanoto; Dani Kusuma; Mila Chrismawati Paseleng; Nobita Triwijayanti (STAI Hubbulwathan Duri, 2025)
The digitalization of school management represents a transformative shift from manual processes to technology-driven systems. This study examines the impact of school management digitalization on enhancing service quality in excellent schools. A descriptive qualitative research approach was employed. Data were collected using questionnaires, interview guidelines, and observation sheets. Instrument validity and reliability were confirmed through expert judgment. The study involved students, teachers, and parents as research participants. Findings indicate that successful school digitalization requires seamless system integration to optimize adaptation and usage. The digitalization process yielded significant improvements in three key areas: accessibility of information, service efficiency, and program evaluation accuracy. Performance indicators showed a 37% increase in service quality, rising from 40% to 77%, demonstrating substantial enhancements in service speed and effectiveness. The study highlights that the positive outcomes of digitalization stem from the integration and user-friendly design of school management systems. Schools that adopt a well-structured digital framework experience greater efficiency, transparency, and stakeholder satisfaction. Digital transformation in school management leads to improved accessibility, service speed, and program evaluation. The findings underscore the importance of an integrated and user-centric approach to digitalization, ensuring enhanced performance and streamlined school operations. Future research should explore long-term impacts and scalability in diverse educational settings.